Development Strategy for Paal Beach Tourist Destination in East Likupang, North Sulawesi, Indonesia - Kapantow, Gene H.M; Tarore, Melissa L.G; Lumingkewas , Jelly R.D (ITScience (Information Technology and Science), 2023)
In order to accelerate the development of the tourism sector, the Indonesian government has designated five tourist destinations in Indonesia as super priority tourist destinations, one of which is East Likupang of North Minahasa Regency in North Sulawesi Province. Paal Beach is one of the main tourist attractions in East Likupang. Even though the beach is very beautiful and the access to it is very good, the number of visits is still far below it's carrying capacity. This research aims to identify appropriate development strategies for the Paal Beach tourist destination to attract more visitors. The analytical tool used is SWOT analysis. The research results show that various external factors are very supportive for the development of Paal Beach. However, the beach still has various weaknesses that could make it unattractive for some people to visit. The main identified weaknesses are related to the lack of adequate infrastuctures and supporting facilities So, the main strategy should be to prioritize improving these infrastuctures and supporting facilities. If infrastuctures and supporting facilities are improved, then this area has great potential to be able to take advantage of the existing external factors identified as opportunities, especially with the designation of East Likupang as one of the super priority tourist destinations in Indonesia.